Environmental conservation in military training areas—source of spatial conflicts? - Seidl, Tomáš; Chromý, Pavel (IGiPZ PAN, 2010)
The aim of the paper is to provide the overview of the spatial development conflicts linked with the existence of Military training areas (MTA) in the regional system. Only several places in the Central European space can be called new wilderness. Above all these are the MTA. The environmental history of these spaces went through a deep reversion. Changes in their cultural, political as well as social-economic profile can be compared with the specific belt of the former Iron Curtain zones only. Last two decades were essential for the physical existence of the MTAs. Because of the weak local political power, social capital and wide public support, are most of the decommitted MTAs in a deep conceptual crisis. The presented study finds solutions based on a long lasting research.
29 cm
Keywords: military area; environmental values; decommittment; core-periphery; Czechia